Analisis Keberterimaan Guru Sekolah Dasar terhadap Media Pembelajaran Multimodalitas Berbasis Google Sites pada Materi Mengenal Peta Menggunakan System Usability Scale - Karmilah, Lilah; Yunus Abidin (Lembaga Teewan Journal Solutions, 2026)
Understanding students’ initial conceptions is a crucial step in designing effective science instruction at the elementary level. This study aims to analyze students’ initial understanding of elementary science concepts through the use of open-ended pre-assessment instruments. A descriptive quantitative approach was employed involving 29 fifth-grade students at an Sekolah Dasar Negeri Hegarmanah 1 Jatinangor . Data were collected through an open-ended pre-assessment administered prior to instruction on the topic “Why Does the Earth Change?”. The instrument consisted of five open-ended questions designed to elicit students’ conceptual understanding, reasoning patterns, and potential misconceptions. Students’ responses were evaluated using an analytic scoring rubric and analyzed using descriptive statistics, including mean, median, standard deviation, and percentage distribution across readiness categories. The findings indicate that the average scores were centered around the middle level, suggesting that most students possessed basic prior knowledge, although their understanding was not yet well developed. The distribution of scores revealed heterogeneous levels of readiness, with students classified into high, middle, and low initial understanding categories. These results highlight the effectiveness of open-ended pre-assessment in revealing variations in students’ prior knowledge and misconceptions, and underscore the importance of using pre-assessment data to support differentiated and adaptive science instruction in elementary classrooms.